Insurance demand under prospect theory: A graphical analysis - Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2012)
This paper analyzes insurance demand under prospect theory in a simple model with two states of the world and fair insurance contracts. We argue that two different reference points are reasonable in this framework, state-dependent initial wealth or final wealth after buying full insurance. Applying the value function of Tversky and Kahneman (1992), we find that for both reference points subjects will either demand full insurance or no insurance at all. Moreover, this decision depends on the probability of the loss: the higher the probability of the loss, the higher is the propensity to take up insurance. This result can explain empirical evidence which has shown that people are unwilling to insure rare losses at subsidized premiums and at the same time take-up insurance for moderate risks at highly loaded premiums.
Keywords: D14; D81; G21; 330; insurance demand; prospect theory; flood insurance; diminishing sensitivity; loss aversion